Byzantium in the seventh century : the transformation of a culture - Haldon, John F. (Cambridge University Press, 1990)
This book presents the first analytical account in English of the major developments within Byzantine culture, society and the state in the crucial formative period from c. 610 to 717. Since its original publication in 1990, the text has been revised throughout to take account of the latest research. The seventh century saw the final collapse of ancient urban civilisation and municipal culture, the rise of Islam, the evolution of patterns of thought and social structure which made imperial iconoclasm possible, and the development of state apparatuses - military, civil and fiscal - typical of the middle Byzantine state. Conflicting ideas of how these changes and developments are to be understood have proliferated in the last fifty years. This book is the first serious attempt to provide a comprehensive, detailed survey of all the major changes in this period.
Keywords: Byzantine Empire -- Civilization -- 527-1081.; Empire byzantin -- Civilisation -- 527-1081.; HISTORY.; Civilization; Byzantine Empire; 527-1081; Electronic books.